Estudio comparativo de los frameworks de desarrollo utilizados en el departamento de sistemas de la UTB. - Pazmiño Carriel, Raúl Anibal (2022)
Creating a new app or website from scratch with pure code takes a lot of work and time, and in higher educational institutions there is never enough time. Sometimes you will have to develop a feature from scratch that some developers have done thousands of times, like a normal contact form, with a lot of wasted time, taking this criteria into account, Frameworks can make your life easier, as they provide a solid foundation to begin development. This research proposal aims to deepen what development frameworks are used in the systems department of the UTB for the development of existing projects and applications in the higher institution, since these frameworks allow the development of web applications with greater code savings, for which The use of these frameworks has been evolving as web programming languages appear, being efficient from every point of view, they are manageable more quickly with the user who wishes to present some type of project or program. In the same way, in the present investigative work, it is described that development frameworks and programming languages are used in the systems department of the Technical University of Babahoyo for the creation of web applications, it is essential to learn and update in the technologies that are with the passing of the years because these new tools could solve problems more easily in the technological field.